2000
DOI: 10.2460/javma.2000.217.1853
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of American trypanosomiasis (Chagas disease) among dogs in Oklahoma

Abstract: Our findings suggest that T. cruzi is enzootic in eastern Oklahoma. Measures that would reduce the risk of dogs acquiring T. cruzi infection are unlikely to be acceptable to their owners, and no effective drugs are available for treatment. The presence of T. cruzi-infected dogs poses a threat of transmission to persons at risk of exposure to contaminated blood Veterinarians who practice in the southern United States should be cognizant of this blood borne zoonosis and educate all personnel about appropriate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 14 publications
2
62
0
5
Order By: Relevance
“…Reports that triatomine contact with domestic dogs presents an increased risk of Chagas disease transmission to humans points toward the need for increased collaboration between epidemiologists, entomologists, and veterinarians in future disease risk predictions (Barr et al, 1995;Bradley et al, 2000;Beard et al, 2003;Enger et al, 2004;Crisante et al, 2006). The results presented here might serve as insight for comprehensive fine-scale studies of areas that are in the margins of the defined higher-risk ranges through a GIS model that utilizes weighted variables acquired from landscape, ecological, and environmental data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports that triatomine contact with domestic dogs presents an increased risk of Chagas disease transmission to humans points toward the need for increased collaboration between epidemiologists, entomologists, and veterinarians in future disease risk predictions (Barr et al, 1995;Bradley et al, 2000;Beard et al, 2003;Enger et al, 2004;Crisante et al, 2006). The results presented here might serve as insight for comprehensive fine-scale studies of areas that are in the margins of the defined higher-risk ranges through a GIS model that utilizes weighted variables acquired from landscape, ecological, and environmental data.…”
Section: Discussionmentioning
confidence: 99%
“…Triatomine samples and autochthonous Chagas disease cases and their proximity to populated areas in the United States. Data sources: Usinger, 1944;Woody and Woody, 1955;Anonymous, 1956;Sjogren and Ryckman, 1966;Lent and Wygodzinsky, 1979;Betz et al, 1984;Ryckman, 1984;Schiffler et al, 1984;Navin et al, 1985;Ochs et al, 1996;Bradley et al, 2000;Herwaldt et al, 2000;Yabsley and Noblet, 2002;ESRI, 2005;NOAA-NGDC, 2007. and 16%, respectively. As is evident from Figure 3, the range at higher risk due to a temperatureinduced increase in triatomine activity will expand northward in the Midwest and north along the Atlantic coast, placing a considerably larger population in the higher risk range for disease transmission.…”
Section: Areas Of Increased Risk Of Chagas Disease Transmissionmentioning
confidence: 99%
“…In certain areas of that state, up to 43% of the raccoons were infected (Pietrzak & Pung 1998). Closer to the human domestic environment, Bradley et al (2000) have shown that 3.6% of rural hunting dogs in Oklahoma were seropositive for T. cruzi. Human infection from the sylvatic environment can occur either from sudden migration of hemiptera to the human environment, forced by the destruction of forests (Maguire et al 1986) or by the ingestion of foods contaminated by hemipteran faeces or crushed insects (Shikanai-Yasuda et al 1991, da Silva Valente et al 1999).…”
Section: The Ecobiology Of T Cruzimentioning
confidence: 99%
“…Several studies have shown the presence of the insect vector as well as infection of domestic dogs and wild animals in the US (Meurs et al 1998, Bradley et al 2000, Beard et al 2003, Yabsley and Noblet 2002. Further, due to signifi cant increases in immigration to the USA and Canada from endemic countries and perinatal transmission, it is estimated that ∼ 100, 000 people residing in USA may be infected with T. cruzi.…”
mentioning
confidence: 99%